THE RESULTS OF NEED ANALYSIS MODEL OF CONTENT COMPLEXITY AND COGNITIVE PROCESS LEVEL ON DYNAMIC FLUID CONCEPTS FOR HIGH SCHOOL PHYSICS LESSON - Fauziah Alkhoriza Syafni; Amali Putra; - Akmam; Wahyuni Satria Dewi (Universitas Negeri Padang, 2022)
In physics learning tools, it is necessary to develop complex knowledge dimensions and high-level thinking skills for students according to the revised Bloom's Taxonomy. The situation in the field, the availability of content according to the dimensions of knowledge and cognitive processes in teacher learning tools that have not been developed properly. The solution is to design the results of the Dynamic Fluid requirements analysis model obtained in the lesson plans, teaching concepts, and instrument evaluations to be used as references to develop content and cognitive processes in other materials. This type of research is Research and Development (R&D) using the Plomp development model. The research instrument is an interview instrument, an assessment instrument and instrument validation. The data were processed using the percentage technique and presented in graphs and tables to be analyzed, interpreted and described. The results of the analysis of the availability of content in teacher learning tools: 48% conceptual, 33% factual, 19% procedural, and 0% metacognitive. cognitive processing availability: remember 20%, understand 37%, apply 22%, analyze 12%, realize 8%, and create 1%. availability of scientific approach: 28% observing, 22% asking, 12% trying, 19% reasoning and 8% communicating. The correct assessment of aspects of content, language, graphics and presentation: RPP 90.5%, Teaching Concept 88.49%, and evaluation instruments 89.9%. Thus, due to the analysis of concept requirements for Dynamic Fluids, the keyword physics learning model meets the very valid criteria and is suitable for use in high school physics learning.